Preparat Anti Jamur Dalam Pencegahan Mukositis Oral Akibat Efek Samping Radioterapi pada Pasien Keganasan Kepala Leher - Henny Kartikawati (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTEffect of anti fungal preparations as oral mucositis prevention from radiotherapy side effects in nasopharyngeal carcinoma patientsBackground: Oral mucositis may lessened food intake and delays the radiation schedule in patients with nasopharyngeal carcinoma. Antifungal treatment fluconazole is known to be effective for treating fungal infections of mucous membrane and systemic infections caused by Candida sp. Itraconazole is also effective in treating fungal infections of mucous membrane or systemic infections. This study proves the effectiveness of fluconazole and itraconazole in the prevention of moderate to severe mucositis.Methods: An experimental study design with pre and post test randomized-control trial. Group A1 received fluconazole as prophylactic treatment, group A2 received itraconazole as prophylactic treatment. Group B was as control or non-prophylaxis. The treatment was given from day 11 to day 26 of radiotherapy (for 3 weeks). The outcome of this study was the incidence of moderate to severe mucositis and the findings of Candida Sp. on moderate to severe mucositis using KOH examination.Results: Moderate to severe mucositis was found in 6 cases in the control group (75%), markedly more than the prophylactic fluconazole group with only 2 cases (25%). The incidence of moderate to severe mucositis was also fewer in the itraconazole group, with only 8 cases (36.36%) compared to control group with 15 cases (68.18%). Examination using KOH showed positive fungal infection was greater in the control group compared to fluconazole and itraconazole groups.Conclusion: Fluconazole and itraconazole are useful in preventing the occurrence of moderate to severe mucositis as the side effects of radiotherapy in nasopharyngeal carcinoma patients, with relative risk reduction (RRR) of 40% for fluconazole and 45.8% ofitraconazole.Keywords: Fluconazole, itraconazole, mucositis, radiotherapyABSTRAKLatar belakang: Mukositis oral dapat menurunkan intake makanan dan tertundanya jadwal radiasi pada pasien keganasan kepala leher. Fluconazole adalah obat anti fungal yang efektif untuk mengobati infeksi jamur pada mukosa dan infeksi sistemik yang disebabkan oleh Candida sp. Itraconazole juga efektif untuk menangani infeksi jamur pada mukosa atau sistemik. Penelitian ini membuktikan efektivitas fluconazole dan itraconazole dalam pencegahan mukositis sedang-berat.Metode: Studi eksperimental dengan desain pre and post test randomized control trial. Kelompok A1 mendapat fluconazole, kelompok A2 menerima itraconazole sebagai perlakuan profilaksis. Kelompok B adalah kontrol atau non profilaksis. Perlakuan diberikan hari ke-11 sampai -26 radioterapi (3 minggu). Outcome penelitian ini berupa jumlah kejadian mukositis sedang-berat dan ditemukannya Candida Sp pada mukositis sedang-berat dengan pemeriksaan KOH.Hasil: Mukositis sedang-berat didapat 6 kasus kontrol (75%), jauh lebih banyak dibanding profilaksis fluconazole (2 kasus/25%). Kelompok itraconazole 8 kasus (36,36%) kejadian mukositis sedang-berat, lebih sedikit dibanding kontrol (15 kasus/68,18%). Penilaian KOH positif jamur lebih banyak pada kelompok kontrol dibanding fluconazole dan itraconazole.Simpulan: Fluconazole dan itraconazole bermanfaat untuk mencegah kejadian mukositis sedang-berat akibat efek samping radioterapi pada penderita karsinoma nasofaring, dengan nilai RRR (relative risk reduction) 40% pada fluconazole dan 45,8% pada itraconazole.